Carbon Anode Materials: A Detailed Comparison between Na‐ion and K‐ion Batteries. Issue 11 (27th January 2021) - Zhang, Lupeng; Wang, Wei (Alex); Lu, Shanfu; Xiang, Yan
Abstract: As novel "post lithium‐ion batteries, " sodium‐ion batteries/potassium‐ion batteries (SIBs/PIBs) are emerging and show bright prospect in large‐scale energy storage applications due to abundant Na/K resources. Further benefits of this technology include, its low cost, chemical inertness and safety. Extensive research findings have demonstrated that carbon‐based materials are promising candidates for both SIBs and PIBs. Although the two alkali‐ion batteries have similar internal components and electrochemical reaction mechanisms, in carbon‐based materials the storage/release behaviors of Na + and K + are not exactly the same. Therefore, a comprehensive comparison of Na + /K + storage behaviors in carbon anode materials is lacking. It is absolutely imperative to understand these mechanisms more clearly to achieve ideal performance. Herein, three potential Na + /K + storage/release behaviors are discussed, which are i) intercalation/deintercalation mechanism, ii) adsorption/desorption mechanism, and iii) pore‐filling mechanism. This review not only attempts to summarize the development status of carbon anode materials (graphite, graphene, hard carbon and soft carbon), but also provides a comprehensive comparison (mechanism, capacity, rate capability, diffusion coefficient, cyclability, potassiation/sodiation potential) between SIBs and PIBs. Finally, critical issues and perspectives are discussed to demonstrate possible development directions for carbon anode materials for SIBs and PIBs. Abstract : This perspective attempts to summarize the development status of four carbon anode materials (graphite, graphene, hard carbon and soft carbon) of sodium‐ion/potassium‐ion batteries (SIBs/PIBs), and comprehensively demonstrates the similarities and differences of Na + and K + storage behaviors in carbon anode materials, which provides good guidance to select and optimize ideal carbon anode materials for high‐performance SIBs/PIBs.